The Effect Of Exercises Using Non – Balanced Strength Device On Improving Maximum Strength And Snatch Achievement In Youth Weightlifters - Mahdi, Marwan; Hashim, Falih (Journal of Physical Education, 2019)
Weightlifting is one of the sports that require great resistance that surpasses the weightlifters’ weight. The problem that faces all weightlifters during jerk phase affect the stability of lifts and its success due to weakness in youth weightlifters specially in the second phase of clean and jerk. The research aimed at designing exercises using non – balance strength device and identifying the effect of these exercises using non – balance strength device. The subjects were (6) youth weightlifters aged (17 – 20) years old who represented the experiential group. The training program was applied for (8) weeks with three training sessions per week. The data was collected and treated using proper statistical operation to conclude that exercises using the non – balance strength device have a significant effect on maximum strength and achievement of clean and jerk in youth weightlifters.